2014
DOI: 10.1161/jaha.114.001109
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width Is Associated With Incident Myocardial Infarction in a General Population: The Tromsø Study

Abstract: BackgroundRed cell distribution width (RDW), a measure of the variability in size of circulating erythrocytes, is associated with mortality and adverse outcome in selected populations with cardiovascular disease. It is scarcely known whether RDW is associated with incident myocardial infarction (MI). We aimed to investigate whether RDW was associated with risk of first‐ever MI in a large cohort study with participants recruited from a general population.Methods and ResultsBaseline characteristics, including RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 47 publications
8
73
0
Order By: Relevance
“…Elevated RDW had been shown to predict poor outcomes in the normal population [15,16], in patients with CAD [2][3][4][5][6], and in patients with HF [8][9][10][11][12]. The present analysis is the first to demonstrate the predictive value of RDW both in patients with ischemic and nonischemic LVSD.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Elevated RDW had been shown to predict poor outcomes in the normal population [15,16], in patients with CAD [2][3][4][5][6], and in patients with HF [8][9][10][11][12]. The present analysis is the first to demonstrate the predictive value of RDW both in patients with ischemic and nonischemic LVSD.…”
Section: Discussionsupporting
confidence: 48%
“…[19]. The results of prospective studies with long-term follow-up (Tromsø and National Health and Nutrition Examination Survey) demonstrate that high RDW values are associated with increased risk of myocardial infarction (MI) and mortality due to CAD in the general population [15,16], and in elderly patients without age-associated diseases [20]. Tonelli et al have shown that RDW is a risk factor for MI, stroke and symptomatic HF in patients with stable CAD [4].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] A prospective study conducted by the National Health and Nutrition Examination Surveys (NHANES) reported that RDW is an independent atherosclerotic risk factor, apart from the conventional risk factors and nutritional deficiencies in patients who did not have CVD. [2] Comprehensive prospective and randomized studies on CHD, MI, HF, and stroke showed that RDW was a strong predictor of the mortality in the middle or older ages.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Comprehensive prospective and randomized studies on CHD, MI, HF, and stroke showed that RDW was a strong predictor of the mortality in the middle or older ages. [3][4][5][6] Studies associated with stroke and RDW usually demonstrate the results related with the severity of stroke, outcome and the course of disease, [14][15][16][17] the relationship between the RDW, CCA-IMT, and CP has been mostly investigated in carotid artery disease studies. [5,8] However, CCA and IMT are subclinical atherosclerotic markers; [9,10] and it seems it would be beneficial, if the relationship between the RDW and atherosclerotic CAS, which increases stroke, is investigated in patients undergoing CEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation